Efficacy of a new biosynthetic bacterial 6-phytase on growth performance, bone mineralization, and nutrient digestibility in nursery and growing pigs - Jlali, Maamer; Hincelin, Clémentine; Manceaux, Celsa; Ozbek, Sarper (Frontiers in Veterinary Science, 2025)
Two studies were carried out to investigate the effects of a novel bacterial biosynthetic 6-phytase on growth performance, bone mineralization, and apparent total digestibility (ATTD) of phosphorus (P) in weaned piglets and growing pigs. They were carried out on 192 weaned piglets with initial body weight (BW): 9.3 ± 1.2 kg (33 days of age) and 360 growing pigs with initial BW: 33.3 ± 4.9 kg (85 days) for 43 and 84 days, respectively, according to a randomized complete block design with three treatments. The treatments were a positive control (PC) diet formulated to meet nutrient requirements, a negative control (NC) diet reduced similarly in calcium (Ca) and digestible P by 0.12% points in piglets and by 0.14, 0.11, and 0.10% points, respectively, in phases 1, 2, and 3 in growing pigs, compared to the PC diet; and the NC diet supplemented with the new 6–phytase at 500 phytase units (FTU) per kg of diet (PHY). The mineral depletion decreased final BW (−6.3%, p = 0.005; −3.0%, p < 0.05), average daily gain (ADG: −8.8%, p = 0.003; −4.3%, p < 0.05), bone ash content (−24.7%, p<0.001; −9.6%, p = 0.005), bone P content (−24.6%, p < 0.001; −6.5%, p = 0.11), and ATTD of P (−11.8% points, p < 0.001; −9.2% points, p < 0.001) and increased the feed–to–gain (F:G) ratio (+2.1%, p < 0.001; +4.7%, p < 0.05) in weaned piglets and growing pigs, respectively. Compared to animals fed the NC diet, phytase addition improved the final BW (+6.5%, p = 0.006, +2.3%, p < 0.05), ADG (+9.0%, p = 0.005, +3.4%, p < 0.05), F:G ratio (−3.1%, p < 0.001, −2.4%, p < 0.05), metacarpal ash content (+27.6%, p < 0.001, +9.3%, p = 0.004), and metacarpal P content (+29.3%, p < 0.001, +7.0%, p = 0.06) in weaned piglets and growing pigs, respectively. The final BW, ADG, and bone ash content in animals fed the NC diet supplemented with phytase were comparable to animals fed the PC diet. The supplementation of phytase to the NC diet improved (P < 0.001) the ATTD of P by 13.5 and 24.6% points (p < 0.001) in weaned piglets and growing pigs, respectively. Compared to the NC diet, phytase supplementation also improved the ATTD of Ca (+7.8% points, p) and N (+2.5% points) in growing pigs. This finding indicates the ability of this novel biosynthetic bacterial 6–phytase to restore performance and bone mineralization in piglets and growing pigs fed P– and Ca–reduced diets.